2013
DOI: 10.1111/are.12242
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing dietary protein sources for Japanese sea bass (Lateolabrax japonicus) with an emphasis on using poultry by-product meal to substitute fish meal

Abstract: This study evaluated the potential of using poultry by‐product meal (PBM) to replace fish meal in diets for Japanese sea bass, Lateolabrax japonicus. Fish (initial body weight 8.5 g fish−1) were fed six isoproteic and isoenergetic diets in which fish meal level was reduced from 400 g kg−1 (diet C) to 320 (diet PM1), 240 (diet PM2), 160 (diet PM3), 80 (diet PM4) or 0 g kg−1 (diet PM5), using PBM as the fish meal substitute. The weight gain (WG), specific growth rate, nitrogen retention efficiency, energy retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 33 publications
5
49
1
Order By: Relevance
“…Likewise, feeding gilthead seabream with the PAP diet (containing poultry meal, blood meal and feather meal) did not increase phosphorus losses to the environment. Phosphorus waste outputs in Japanese seabass ( Lateolabrax japonicus ) increased with high inclusion levels of dietary poultry meal (Wang et al, ), but similarly to our study, feeding giant croaker ( Nibea japonica ) on a diet based on poultry meal and feather meal did not increase phosphorus losses (Wu et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Likewise, feeding gilthead seabream with the PAP diet (containing poultry meal, blood meal and feather meal) did not increase phosphorus losses to the environment. Phosphorus waste outputs in Japanese seabass ( Lateolabrax japonicus ) increased with high inclusion levels of dietary poultry meal (Wang et al, ), but similarly to our study, feeding giant croaker ( Nibea japonica ) on a diet based on poultry meal and feather meal did not increase phosphorus losses (Wu et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…These PAP are valuable feed ingredients, as they are waste from food production and are available in large amounts in the EU (Jędrejek, Levic, Wallace, & Oleszek, ). Recent studies indicate that these are suitable alternatives to fishmeal in practical fish diets (Campos, Matos, Marques, & Valente, ; Karapanagiotidis, Psofakis, Mente, Malandrakis, & Golomazou, ; Lu, Haga, & Satoh, ; Wang, Wang, Ji, Han, & Li, ; Wu, Ren, Chai, Li, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Takagi et al () reported that fish meal can be completely replaced with PBM in diets for red sea bream, Pagrus major . The higher dietary fish meal level for golden pompano, compared with that for red drum (Kureshy et al ), red sea bream (Takagi et al ), cuneate drum (Wang et al ), Malabar grouper (Li et al ), and Japanese seabass (Wang et al ), indicates that golden pompano has a limited capacity in utilizing PBM as a fish meal substitute.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rate and feed utilization efficiency generally decrease when dietary fish meal is substituted with PBM (Steffens ; Nengas et al ; Kureshy et al ; Wang et al ; Li et al ) or SBM (McGoogan and Gatlin ; Lim et al ; Tomas et al ; Wang et al ; Hernandez et al ; Kasper et al ; Martinez‐Llorens et al ; Lim et al ; Ye et al ) at high levels. However, partial replacement of dietary fish meal with PBM can improve growth performance of red sea bream (Takagi et al ), gibel carp, Carassius auratus gibelio (Yang et al ), and Japanese seabass (Wang et al ). In this study, fish experienced greater WG when fish meal was substituted by PBM at the same level than when fish meal was substituted by SBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation